Two ticking time bombs: giant coronary artery aneurysm and abdominal aortic aneurysm in the setting of urgent vascular surgery—a case report. Issue 5 (12th October 2020) - Schukraft, Sara; Carrel, Thierry; Togni, Mario; Attinger-Toller, Adrian
Abstract: Background: Giant coronary artery aneurysms (CAAs) are rare and treatment strategies various, especially in the setting of a concomitant abdominal aortic aneurysm (AAA) which needs urgent repair. Case summary: A 78-year-old Caucasian male was admitted for evaluation of a rapidly expanding AAA. In addition, computed tomography angiography revealed a 5 x 4 cm giant aneurysm of the right coronary artery. After interdisciplinary discussion, the patient underwent aorto-bi-iliac bypass grafting first. In a second step, CAA was successfully excluded and coronary artery bypass grafting of the right coronary artery was performed. Discussion: Treatment strategy of CAA and timing of non-cardiac surgery is challenging. In order to minimize the overall risk of rupture interdisciplinary discussion is crucial. In our case, aorto-bi-iliac bypass grafting was safely performed, and the patient underwent successful CAA excision in a second step.